The Possible Effects of Sodium Nitrite and Sodium Benzoate as Food Additives on The Liver in Male Rats - Radwan, Eman Hashem; MM Elghazaly; KK Abdel Aziz; AI Barakat; H Kh Hussein (JOURNAL OF ADVANCES IN BIOLOGY, 2020)
Common food additives endorsed by Food and drug Organization "FDA" are utilized to preserve taste. The display think about examined the perilous impacts of sodium nitrite, sodium benzoate and their blend which utilized in fabricating of the food additives on a few biochemical parameters and histo-pathological examination in male rats. Male rats were divided into four groups; group I utilized as control, group II and III were treated orally with sodium nitrite NaNO2 (80 mg/kg BW) and sodium benzoate (SB) (200 mg/kg BW), separately. Group IV was treated orally with the blend of sodium nitrite and sodium benzoate. Rats were managed their dosages each day for 8 weeks. It appeared that sodium nitrite, sodium benzoate and their blend (NaNO2 and SB) initiated a critical increment within the serum levels of aspartate aminotransferase "AST", alanine aminotransferase "ALT". Antioxidant proteins (GSH, CAT) within the liver tissue recorded a decrease while, MDA recorded an increase action level within the tested groups. Over expression in p53 happened in exploratory groups which were treated by NaNO2, SB and their blend. The present study concluded that the blend of food additives can actuate harmfulness within the liver of rats. In conclusion, it is noted that food additives induced hepatotoxicity within the liver. It diminished the antioxidant chemicals (GSH, CAT) and elevated the activity level of the MDA and increment tumor silencer quality p53 in liver tissue. Food additive substances caused changes in biochemical parameters (ALT, AST). The utilization of food additives must be diminished. The usage of the mixture of sodium nitrite and sodium benzoate induced changes in biochemical parameters and immune-histopathology.